Geochronology of a long Pleistocene sequence at Kilombe volcano, Kenya: from the Oldowan to Middle Stone Age. (January 2021) - Hoare, S.; Brink, J.S.; Herries, A.I.R.; Mark, D.F.; Morgan, L.E.; Onjala, I.; Rucina, S.M.; Stanistreet, I.G.; Stollhofen, H.; Gowlett, J.A.J.
Abstract: We report a newly extended stratigraphic sequence with associated Palaeolithic sites from the area of the extinct Kilombe volcano in central Kenya. The extended archaeological sequence runs from Oldowan finds, through the Acheulean, and up to the Middle Stone Age. The sedimentary sequences within the Kilombe caldera and south flanks of the mountain have been dated through 40 Ar/ 39 Ar measurements and palaeomagnetic studies. A series of 40 Ar/ 39 Ar values date the geological sequence from 2.493 ± 0.095 Ma, near the beginning of the Lower Pleistocene, through to 0.118 ± 0.030 Ma near the Middle to Upper Pleistocene transition. It includes the first entirely new area of Oldowan localities in East Africa south of Ethiopia for thirty years, and the first in a rugged mountainous setting. Trachyte lavas of Kilombe mountain were extruded during and after c. 2.5 Ma, followed by formation of a caldera and subsequent caldera lake, and sedimentation of a sequence of tuffs, diamictites, sandstones, and claystones. Sections in the mid-part of this intra-caldera fill-sequence have produced dates of 1.8–1.7 Ma, associated with an Oldowan industry and fauna dated precisely at 1.814 ± 0.004, and overlain by Acheulean finds at higher level. On the southern outward flanks of Kilombe mountain, a second major sequence is bounded at the base by trachyphonolite and a tuff yielding dates in the range 1.58–1.50 Ma. The main Acheulean archaeological site (GqJh1) falls within the overlying sedimentary sequence and has an age of c. 1.0 Ma, on the basis of a new 40 Ar/ 39 Ar date for the Three-Banded Tuff and palaeomagnetic reversal stratigraphy. Further 40 Ar/ 39 Ar dates indicate an age of c. 0.48–0.46 Ma for a marker ashflow tuff (AFT), prominent across the area. At Moricho, west of Kilombe, sediments above the AFT have been dated in the range 270, 000–120, 000 years and are associated with Middle Stone Age assemblages. In total, these sites attest to hominin activity from an Oldowan horizon dated to 1.8 Ma up to Later Stone Age stone scatters within the last 100, 000 years. Highlights: Kilombe volcano preserves an end-to-end Pleistocene record dated by Argon 40 /Argon 39 and palaeomagnetism. The volcano formed ~2.5 Ma and before 1.8 Ma developed a caldera lake attracting animals and hominins. New Oldowan and Acheulean industries are represented in strikingly high-altitude occupations of landscape. Sedimentary sequences on the mountain southern flank date up to ~1.58 Ma and include Acheulean and MSA industries. The AFT marker tuff dated to ~0.48 Ma overlies the latest Acheulean, and underlies a series of early MSA occurrences.